2019
DOI: 10.1177/1056789519881488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study on effect of braiding angle on low-velocity transverse punch response of braided composite tube

Abstract: In this study, the performance of braided composite tubes under low-velocity transverse impact loading at mid-span was investigated using both numerical and experimental methods. Three types of braided composite tubes with different braiding angles (30°, 45°, and 60°) were manufactured. The transverse punch behavior of the tubes was examined on a low-velocity imspact test bench. A meso-level finite element model of the composite tube was also established for identifying the damage initiation and development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…[4][5][6] To find out the influence of the braided structures on the mechanical performance of tubular braided composites, much research has been done to numerically simulate the braiding process. [7][8][9][10] Many researches have demonstrated that braiding angle is one of the parameters that have a significant influence on the mechanical properties of tubular braided composites. [11][12][13][14] Studies on tubular braided composites under tensile loadings have been investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] To find out the influence of the braided structures on the mechanical performance of tubular braided composites, much research has been done to numerically simulate the braiding process. [7][8][9][10] Many researches have demonstrated that braiding angle is one of the parameters that have a significant influence on the mechanical properties of tubular braided composites. [11][12][13][14] Studies on tubular braided composites under tensile loadings have been investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…They are fabricated by using a radial braider or Maypole braider and are manufactured with different braiding patterns including diamond (1/1), regular (2/2), hercules (3/3), and tri‐axial (diamond or regular with axial yarns) 4–6 . To find out the influence of the braided structures on the mechanical performance of tubular braided composites, much research has been done to numerically simulate the braiding process 7–10 . Many researches have demonstrated that braiding angle is one of the parameters that have a significant influence on the mechanical properties of tubular braided composites 11–14 .…”
Section: Introductionmentioning
confidence: 99%
“…The development of a computational model, which predicts the initiation and propagation of the damage in composite structures is a key aspect for a more comprehensive understanding of the behavior of these structures. For this purpose, the finite element (FE) analysis was used to enhance the accuracy of multiscale modeling (Jin et al., 2020; Wei et al., 2022; Wu et al., 2019). Furthermore, continuum damage mechanics (CDM) (Gao and Wang, 2021; Isometsä and Sjölind, 1999; Ribeiro et al., 2012) and micromechanical damage models (Liu et al., 2020; Zhu et al., 2021) have been used successfully.…”
Section: Introductionmentioning
confidence: 99%